Effects of acidosis on the structure, composition, and function of adult murine femurs. (February 2021) - Peterson, Anna K.; Moody, Mikayla; Nakashima, Iris; Abraham, Ron; Schmidt, Tannin A.; Rowe, David; Deymier, Alix
Abstract: Physiologic pH is maintained in a narrow range through multiple systemic buffering systems. Metabolic Acidosis (MA) is an acid-base disorder clinically characterized by a decrease in systemic pH and bicarbonate (HCO3 − ) levels. Acidosis affects millions annually, resulting in decreased bone mineral density and bone volume and an increased rate of fracture. We developed an adult murine model of diet-induced metabolic acidosis via graded NH4 Cl administration that successfully decreased systemic pH over a 14 day period to elucidate the effects of acidosis on the skeletal system. Blood gas analyses measured an increase in blood calcium and sodium levels indicating a skeletal response to 14 days of acidosis. MA also significantly decreased femur ultimate strength, likely due to modifications in bone morphology as determined from decreased microcomputed tomography values of centroid distance and area moment of inertia. These structural changes may be caused by aberrant remodeling based on histological data evidencing altered OCL activity in acidosis. Additionally, we found that acidosis significantly decreased bone CO3 content in a site-specific manner similar to the bone phenotype observed in human MA. We determined that MA decreased bone strength thus increasing fracture risk, which is likely caused by alterations in bone shape and compounded by changes in bone composition. Additionally, we suggest the temporal regulation of cell-mediated remodeling in MA is more complex than current literature suggests. We conclude that our model reliably induces MA and has deleterious effects on skeletal form and function, presenting similarly to the MA bone phenotype in humans. Graphical abstract: Image, graphical abstract